2008
DOI: 10.3382/ps.2007-00504
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters for Contents of Intramuscular Fat and Inosine-5′-Monophosphate and Carcass Traits in Chinese Beijing-You Chickens

Abstract: This study was conducted to estimate genetic parameters of meat quality-related traits by a MTDFREML procedure, using 1,069 purebred Beijing-You full-sib male chickens derived from the first 2 generations of divergent selection for the percentage of intramuscular fat (IMF) and selection for increased inosine-5'-monophosphate content (IMP) in breast meat. The results show that estimated heritability of IMP was moderate (0.23), and heritability of IMF was low (0.11). Other traits with high heritabilities, rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 28 publications
1
27
1
Order By: Relevance
“…The heritability estimate for AF (0.80±0.08) was also high, indicating that this trait can respond very well to selection. Chen et al (2008) worked with Beijing-You birds and obtained a heritability estimate of 0.62, close to those reported in the present study, whereas Lotfi et al (2011), while studying quails, found heritability estimates of 0.28±0.06 for AF, different from those obtained here.…”
Section: Resultscontrasting
confidence: 50%
“…The heritability estimate for AF (0.80±0.08) was also high, indicating that this trait can respond very well to selection. Chen et al (2008) worked with Beijing-You birds and obtained a heritability estimate of 0.62, close to those reported in the present study, whereas Lotfi et al (2011), while studying quails, found heritability estimates of 0.28±0.06 for AF, different from those obtained here.…”
Section: Resultscontrasting
confidence: 50%
“…According to our results, selection for decreasing carcass fatness by reducing AFP should not lead to any significant change in IMF, which is known to influence sensorial characteristics of the meat such as juiciness and flavour [7]. Similarly, the studies by Chen et al [17] and Zerehdaran et al [15] failed to demonstrate any significant correlation between the deposition of abdominal fat and that of intramuscular fat in breast muscle, whereas a positive genetic correlation was reported between abdominal and subcutaneous fat. On the other hand, our results indicated that selection for lower carcass fatness should increase the intensity of the red and yellow colour of breast meat, especially in males in which a strong genetic link between AFP and body weight was also found.…”
Section: Discussionmentioning
confidence: 77%
“…However, since IMP content is greatly influenced by nutrition, breeds, and storage time, more work should be performed from both of those selection aspects. The limited number of studies about the heritability of IMP in chicken and other species showed that IMP has low heritability [22]. In the experimental population, the IMP content showed a large coefficient of variance (12.7% and 17.6%), indicating that IMP had a possibility for improvement.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 91%